A sustainist lexicon : seven entries to recast the future - rethinking design and heritage - Schwarz, Michiel; Knoop, Riemer R.; Elffers, Joost (Amsterdam : Architectura & Natura Press, 2016)
Words are our first tools for making sense of the world. This publication presents seven words for a changing time. In this timely exploration of our cities, heritage, civic initiatives, urbanism and the future, Michiel Schwarz, co-creator of the Sustainism manifesto, charts how a new ethos and praxis is emerging in the 'design' of our living environment. This concise lexicon explores the changing cultural landscape through seven entries: Placemaking, Connectedness, Local, Commons, Circularity, Proportionality, Co-Design. In doing so it marks inroads into a sustainist culture that is more connected, locally-rooted, collaborative, respectful of the human scale, and altogether more environmentally and socially sustainable.
boek
Keywords: Sustainability -- Philosophy; Sustainable development; Sustainable living; Sustainable design